2017
DOI: 10.1002/mrd.22812
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐editing technologies to improve research, reproduction, and production in pigs

Abstract: The ability to directly manipulate the pig genome through genetic engineering has been available to the research community for over three decades. This technology has progressed from the random insertion of foreign DNA, via a variety of techniques (pronuclear microinjection, sperm mediated gene transfer, and integration of mobile genetic elements), to manipulation of endogenous genes, via homologous recombination in somatic cells followed by somatic cell nuclear transfer. Over the last few years, designer nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
0
22
0
2
Order By: Relevance
“…With the ever-widening application of genetically modified mice and other laboratory animal species, it is increasingly useful to have validated immunohistochemical markers for humans that function across laboratory animal species. 40,50 Mice likely will continue to be used extensively in translational research, because they provide a wide range of genetic models, have a short life span and high reproductive fecundity, and are inexpensive to house. However, some of the challenges and pitfalls in translating mouse research studies to humans have garnered increased attention recently.…”
Section: Discussionmentioning
confidence: 99%
“…With the ever-widening application of genetically modified mice and other laboratory animal species, it is increasingly useful to have validated immunohistochemical markers for humans that function across laboratory animal species. 40,50 Mice likely will continue to be used extensively in translational research, because they provide a wide range of genetic models, have a short life span and high reproductive fecundity, and are inexpensive to house. However, some of the challenges and pitfalls in translating mouse research studies to humans have garnered increased attention recently.…”
Section: Discussionmentioning
confidence: 99%
“…In agriculture, SCNT can rescue endangered species, protect the genetic resources of commercially important species, and accelerate the propagation of breeding livestock, including pigs, cows, and sheep (Gomez et al, 2009;Keefer, 2015). In combination with genome-modification technologies such as the recently developed clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9mediated genome editing, SCNT can rapidly produce cloned mammals with desirable traits including rapid growth, disease resistance, and good meat quality, thereby cultivating novel varieties, and shortening breeding cycle (Galli et al, 2012;Wells and Prather, 2017;Lee et al, 2020). In biomedicine, SCNT can create a mammary gland bioreactor to produce therapeutic proteins, establish animal models to investigate the pathogenesis of human diseases, and produce genetically modified xenograft organs for patient transplantation (Lotti et al, 2017;Niu et al, 2017;Telugu et al, 2017).…”
Section: Scnt In Mammalsmentioning
confidence: 99%
“…The deliberate introduction of double-stranded DNA breaks at the desired integration site should therefore improve the efficiency of heterologous DNA insertion by activating and recruiting the cellular repair machinery. Application of ZFN, TALEN and CRISPR technologies have shown that homologous recombination efficiencies are improved when one or more doublestrand DNA breaks are introduced into the genome at the desired site of insertion [67] with CRISPR exhibiting bi-allelic targeting rates as high as 90% [68]. The use of these more advanced genome engineering tools has greatly improved the rates and specificity of both gene deletion and gene insertion in genomes.…”
Section: Homologous Recombinationmentioning
confidence: 99%